2010
DOI: 10.1177/0003319710382416
|View full text |Cite
|
Sign up to set email alerts
|

Fibrin D-Dimer Concentration, Deep Vein Thrombosis Symptom Duration, and Venous Thrombus Volume

Abstract: Despite varying symptom duration prior to diagnosis, fibrin D-dimer remains a sensitive measure of venous thrombosis and correlates with thrombus volume.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 13 publications
0
17
0
1
Order By: Relevance
“…In that review, both sensitivity and negative predictive values (NPV) were 100%, when both clinical assessment and DD were used; but dropped to 80% and 95%, respectively, when only DD was used. In our report, the need for VDU dropped exponentially from using DD alone, using Wells criteria alone, to Wells criteria (3) and DD; from 84, to 44, to 27%, respectively.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…In that review, both sensitivity and negative predictive values (NPV) were 100%, when both clinical assessment and DD were used; but dropped to 80% and 95%, respectively, when only DD was used. In our report, the need for VDU dropped exponentially from using DD alone, using Wells criteria alone, to Wells criteria (3) and DD; from 84, to 44, to 27%, respectively.…”
Section: Discussionmentioning
confidence: 62%
“…Studies have demonstrated DD as a sensitive and accurate essay to correlate, not only with the presence, but also with the volume of thrombus. (3) In addition, DD has a negative predictive value >95%, which allows for exclusion of VTE in selected patients. (49) A metaanalysis(10) conducted over three decades reported that enzyme-linked immunosorbent assays (ELISA), in general, dominate the comparative ranking among all DD assays for sensitivity, negative likelihood ratio, and a negative result on quantitative rapid ELISA, which is as diagnostically useful as venous duplex ultrasound (VDU) findings.…”
Section: Introductionmentioning
confidence: 99%
“…In patients with pulmonary embolism, the D‐dimer concentration is related to thrombus volume assessed by contrast‐enhanced CT,29 and a high D‐dimer concentration of >5000 ng/mL is a risk factor for in‐hospital mortality 30. Similarly, in patients with deep vein thrombosis, the ultrasound‐based estimated thrombus volume correlates with the D‐dimer concentration 31. These findings are consistent with the finding that D‐dimer elevation is associated with extensive aortic dissection 12, 13, 14.…”
Section: Discussionmentioning
confidence: 99%
“…28 However, the duration of symptoms is known to be a poor measure of thrombus volume and characteristics. 36 Furthermore, thrombus itself may be heterogeneous, with older and fresher components. Although the ATTRACT trial will add to consideration of optimal timing for intervention in the setting of acute proximal thrombosis based on symptom duration, the effect of thrombus heterogeneity and actual thrombus age may be difficult to elucidate.…”
Section: Case Selectionmentioning
confidence: 99%